Pirolisis Kulit Pinus Merkusii Menjadi Bio-Oil Menggunakan Katalis Mo/Lempung Cengar - Inget Yester Yunanda; Syaiful Bahri; Edy Saputra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Increasing population and industrial activities in Indonesia caused the consumption of petroleum increased while petroleum reserves continue to decline, so is very important of searching for alternative energy sources instead of petroleum. the biomass of pine bark considered as waste that pollutes the environment it can be used as source of fuel to produce bio-oil by means of pyrolysis using catalyst Mo/ Clay. The purpose of this research is to make bio-oil from pine bark using a catalyst Mo/clay by pyrolysis process, as well as test physical properties of the bio-oil, and to determine the effect of variation the carrier of the catalyst metal catalyst weight variations against of biomass. In this research pine of bark by the size of -60+80 mesh, 50 grams, 500 ml silinap and catalyst Mo / clay inserted into of pyrolysis reactor. This process conducted at a temperature 320oC and the stirring speed of 300 rpm operate for about 120 minutes by flowing nitrogen gas. For the optimum yields obtained at 1% catalyst Mo/clay as much as 9% of biomass that is equal to 68.46%. The test results physical properties obtained density of 0.78 g/ml, 1.77 cSt viscosity, acidity 25.79 mg NaOH /g sample and the flash point 54oC. Results of analysis compound chemical using GC-MS, obtained the dominant chemical components in the bio-oil is 2-Pentene 19.05%, 1-Pentene 9.88%, 8.72% Cyclohexane, Pentane 7.7% and Silane 3, 32%.Keywords: biomass, bio-oil, catalyst mo/clay, pine bark, pyrolysis